Two-component polyurethane heat-conducting gel and preparation method thereof

A two-component polyurethane thermal conductive gel addresses environmental and curing issues of silicone-based materials by using specific components, achieving high temperature resistance and low thermal conductivity, maintaining performance under severe aging conditions.

CN119193092AInactive Publication Date: 2024-12-27HANGZHOU ZHIJIANG SILICONE CHEM +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411586559.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing thermal interface materials, particularly those based on silicone resins, face environmental concerns due to the presence of D4-D10 silicone ring bodies and issues with incomplete curing, leading to safety hazards and environmental damage, while single-component MS thermal conductive gels do not achieve true non-siliconization and are prone to incomplete curing.

Method used

A two-component polyurethane thermal conductive gel composed of components A and B, with specific ratios and ingredients such as polyol, plasticizer, thermally conductive powder, and catalysts, is developed to address these issues, ensuring high temperature resistance and low thermal conductivity without silicon.

Benefits of technology

The polyurethane gel achieves excellent high temperature resistance, low thermal conductivity, and maintains performance under extreme aging conditions, overcoming the limitations of silicone-based materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119193092A_ABST
    Figure CN119193092A_ABST
Patent Text Reader

Abstract

The invention provides two-component polyurethane heat-conducting gel. The two-component polyurethane heat-conducting gel is prepared from a component A and a component B in a volume ratio of (0.8-1.2): 1, the component A comprises the following components in parts by weight: 5-15 parts of polyol; 1-10 parts by weight of a plasticizer; 80-95 parts by weight of heat conducting powder; 0.1-1 part by weight of a dispersant; 0.1-1 part by weight of a catalyst; 0.1-1 part by weight of yellow color paste; the component B comprises the following components in parts by weight: 2-10 parts of isocyanate; 2-10 parts by weight of a polyol; 2-10 parts by weight of a plasticizer; 80-95 parts by weight of heat conducting powder; 0.1-1 part by weight of an anti-aging agent; 0.1-1 part by weight of a dispersant; 0.1-1 part by weight of a water absorbent; and 0.1-1 part by weight of blue color paste. Compared with the prior art, the two-component polyurethane heat-conducting gel provided by the invention adopts specific components with specific contents, realizes relatively good overall interaction, can meet the non-silicon requirement of a thermal interface material, and has excellent high temperature resistance and low heat conductivity coefficient.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermal conductive gel, and more specifically to a two-component polyurethane thermal conductive gel and a preparation method thereof. Background Art

[0002] At present, thermal interface materials play an irreplaceable role in the fields of new energy vehicle power batteries, consumer electronics, etc. The so-called thermal interface material is a material that can conduct heat away from the heat source through itself, which requires itself to have a high thermal conductivity and a thin thickness. At the same time, since the thermal interface material is in direct contact with the heat source, it will be in a high temperature state for a long time, and there are strict requirements on the high temperature resistance of the thermal interface material. The common products on the market are thermally conductive gaskets, thermally conductive gels, thermally conductive silicone greases, etc. prepared based on silicone resins. Since silicone products have good temperature resistance and are soft, they are more suitable for actual industrial and mining use. Other resins such as polyurethane, epoxy, acrylic, etc. have not been used for the time being.

[0003] However, silicone products face an unsolvable problem, namely environmental protection. As we all know, silicone resin contains D4~D10 silicone ring bodies, which are easy to precipitate and cause environmental damage. The EU has gradually begun to restrict the use of silicone materials, and it has become an emerging field for downstream customers to use non-silicon thermal interface materials to replace traditional silicone thermal interface materials.

[0004] In recent years, the solution to the above problems that has emerged in the existing technology is to use single-component MS (modified silane) glue to prepare thermal conductive gel. Since silane-modified polymers only have siloxane groups at the polymer ends, the appearance of organic silicon rings is avoided. However, there are still two problems with single-component MS thermal conductive gels. First, there is still silicon in the system, and it has not achieved true non-siliconization; second, the curing method of single-component MS thermal conductive gels is moisture curing, and in the packaging of electronic components, it is very likely that the curing will be incomplete due to the lack of contact with air, which will cause safety hazards. Summary of the invention

[0005] In view of this, the object of the present invention is to provide a two-component polyurethane thermally conductive gel and a preparation method thereof. The two-component polyurethane thermally conductive gel provided by the present invention is based on a polyurethane system, which can meet the requirements for non-silicon thermal interface materials, and the product has excellent high temperature resistance and low thermal conductivity.

[0006] The present invention provides a two-component polyurethane thermal conductive gel, which is composed of a component A and a component B in a volume ratio of (0.8-1.2):1; The A component includes: 5 to 15 parts by weight of polyol; 1 to 10 parts by weight of plasticizer; 80 to 95 parts by weight of thermally conductive powder; Dispersant 0.1 to 1 part by weight; 0.1 to 1 part by weight of catalyst; 0.1 to 1 part by weight of yellow color paste; The B component includes: 2 to 10 parts by weight of isocyanate; 2 to 10 parts by weight of polyol; 2 to 10 parts by weight of plasticizer; 80 to 95 parts by weight of thermally conductive powder; 0.1 to 1 part by weight of an anti-aging agent; Dispersant 0.1 to 1 part by weight; 0.1 to 1 part by weight of water absorbent; 0.1 to 1 part by weight of blue color paste.

[0007] Preferably, the polyol is a flexible aliphatic modified castor oil polyol.

[0008] Preferably, the plasticizer is a hydrocarbon high boiling point plasticizer.

[0009] Preferably, the thermally conductive powder is selected from one or more of Jinge JAZ-386, Jinge JAZ-387, and Zexi CCG060D08G.

[0010] Preferably, the dispersant is selected from BYK BYK-9076 and / or BYK BYK-145.

[0011] Preferably, the catalyst is selected from Umicore Valikat Bi1610 and / or Vertellus Coscat 83.

[0012] Preferably, the isocyanate is an aliphatic polyisocyanate; The water absorbent is selected from Borchers TI and / or LANXESS Trixene ASF.

[0013] The present invention also provides a method for preparing the two-component polyurethane thermally conductive gel described in the above technical solution, comprising the following steps: a) Heat the polyol, plasticizer and thermal conductive powder to 110°C~130°C, mix and dehydrate in vacuum, then cool to below 50°C, add dispersant, catalyst and yellow color paste, mix in vacuum to obtain component A; b) After the isocyanate, the dehydrated polyol and the plasticizer are reacted for the first time, the dried thermal conductive powder, the antioxidant, the dispersant, the water absorbent and the blue color paste are added to carry out a second reaction to obtain component B; c) mixing the above component A and component B in a volume ratio of (0.8-1.2):1 to obtain a two-component polyurethane thermal conductive gel; There is no order restriction for step a) and step b).

[0014] Preferably, the mixing method of heating to 110°C to 130°C in step a) is stirring, and the stirring speed is 400rpm to 600rpm; The vacuum degree of the vacuum dehydration is -0.08MPa~-0.1MPa, and the time is 1.5h~2.5h; The vacuum degree of the vacuum mixing is -0.08MPa~-0.1MPa, the rotation speed is 50rpm~150rpm, and the time is 30min~60min.

[0015] Preferably, the temperature of the first reaction in step b) is 70°C to 90°C, the rotation speed is 80rpm to 120rpm, the vacuum degree is -0.08MPa to -0.1MPa, and the time is 1.5h to 2.5h; The temperature of the second reaction is 10°C to 40°C, the rotation speed is 180rpm to 220rpm, the vacuum degree is -0.08MPa to -0.1MPa, and the time is 0.5h to 1.5h.

[0016] The invention provides a two-component polyurethane thermally conductive gel, which is composed of a component A and a component B in a volume ratio of (0.8-1.2):1; the component A comprises: 5-15 parts by weight of polyol; 1-10 parts by weight of plasticizer; 80-95 parts by weight of thermally conductive powder; 0.1-1 part by weight of dispersant; 0.1-1 part by weight of catalyst; and 0.1-1 part by weight of yellow color paste; the component B comprises: 2-10 parts by weight of isocyanate; 2-10 parts by weight of polyol; 2-10 parts by weight of plasticizer; 80-95 parts by weight of thermally conductive powder; 0.1-1 part by weight of anti-aging agent; 0.1-1 part by weight of dispersant; 0.1-1 part by weight of water absorbent; and 0.1-1 part by weight of blue color paste. Compared with the prior art, the two-component polyurethane thermally conductive gel provided by the present invention adopts specific components in specific contents to achieve better overall interaction, which can meet the requirements for non-silicon thermal interface materials. At the same time, the product has excellent high temperature resistance and low thermal conductivity.

[0017] In addition, the preparation method provided by the present invention has simple process, mild conditions, easy control, low requirements on equipment, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The PCT aging (120°C / 100% RH / 0.2 MPa) hardness change curves of Examples 1 to 3; Figure 2 The high temperature and high humidity aging (85°C / 85%RH) hardness change curves of Examples 1 to 3; Figure 3 : This is the high temperature aging (150°C / 50%RH) hardness change curve of Examples 1 to 3. DETAILED DESCRIPTION

[0019] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] The present invention provides a two-component polyurethane thermal conductive gel, which is composed of a component A and a component B in a volume ratio of (0.8-1.2):1; The A component includes: 5 to 15 parts by weight of polyol; 1 to 10 parts by weight of plasticizer; 80 to 95 parts by weight of thermally conductive powder; Dispersant 0.1 to 1 part by weight; 0.1 to 1 part by weight of catalyst; 0.1 to 1 part by weight of yellow color paste; The B component includes: 2 to 10 parts by weight of isocyanate; 2 to 10 parts by weight of polyol; 2 to 10 parts by weight of plasticizer; 80 to 95 parts by weight of thermally conductive powder; 0.1 to 1 part by weight of an anti-aging agent; Dispersant 0.1 to 1 part by weight; 0.1 to 1 part by weight of water absorbent; 0.1 to 1 part by weight of blue color paste.

[0021] The invention provides a two-component polyurethane thermally conductive gel, which solves the problem that the existing thermally conductive gels are all organic silicon systems and cannot meet the requirement that the glue does not contain free silicon. The present invention adopts polyurethane to replace silicone as the thermal conductive gel. First, the hardness problem needs to be solved. Under actual use conditions, the hardness of the thermal conductive gel cannot be too high. The hardness of the currently used product is in the range of Shore-00 50-70. For silicone, since the silicone chain segment is soft and has low polarity, it is relatively easy to achieve low hardness. However, for the polyurethane system, since its own polarity is relatively high and the urethane in the molecular chain segment is a rigid chain segment, it is difficult to achieve a hardness of Shore-00 level; secondly, the problem of the amount of thermal conductive powder added needs to be solved. The thermal conductive gel has a high requirement for the thermal conductivity, which is usually required to be greater than 3.0 W / m·k. The viscosity of the polyurethane system is relatively large, and the amount of thermal conductive powder added is limited, so it is difficult to achieve a high thermal conductivity; thirdly, the weather resistance of the polyurethane glue. The thermal conductive gel directly contacts the heat source, and has high requirements for the high temperature and high humidity resistance of the glue. It is necessary to ensure that the glue does not crack, does not powder, and has no drastic change in hardness after aging at high temperature and high humidity.

[0022] In order to solve the above technical problems and obtain a thermally conductive gel that can meet the requirements, the present invention starts from the following perspectives: selecting aliphatic isocyanate to reduce the NCO content of the prepolymer, increase the length of the prepolymer chain segment, and improve the flexibility of the glue; selecting a suitable plasticizer to further reduce the hardness of the glue, and reduce the viscosity of the system, and increase the amount of thermally conductive powder added; selecting an efficient wetting and dispersing agent to reduce the viscosity of the system and increase the amount of thermally conductive powder added; selecting a suitable polyol resin to improve the weather resistance of the glue.

[0023] In the present invention, the two-component polyurethane thermally conductive gel is composed of component A and component B in a volume ratio of (0.8-1.2):1, preferably 1:1.

[0024] In the present invention, the A component comprises: 5 to 15 parts by weight of polyol; 1 to 10 parts by weight of plasticizer; 80 to 95 parts by weight of thermally conductive powder; Dispersant 0.1 to 1 part by weight; 0.1 to 1 part by weight of catalyst; 0.1 to 1 part by weight of yellow color paste; It is preferably prepared from the following raw materials: 5 to 10 parts by weight of polyol; 1 to 3 parts by weight of plasticizer; 85 to 92 parts by weight of thermally conductive powder; 0.5 to 1 part by weight of dispersant; 0.5 to 1 part by weight of catalyst; 0.4 to 0.6 parts by weight of yellow color paste.

[0025] In the present invention, the polyol is preferably a flexible aliphatic modified castor oil polyol; the flexible aliphatic modified castor oil polyol is preferably selected from Itoh Oil URIC 4048U and / or Itoh Oil URIC PH-100D, more preferably Itoh Oil URIC 4048U or Itoh Oil URIC PH-100D. The present invention has no particular limitation on the source of the polyol, and commercially available products known to those skilled in the art can be used.

[0026] In the present invention, the plasticizer is preferably a hydrocarbon high boiling point plasticizer; the hydrocarbon high boiling point plasticizer is preferably Rutgers Ruetasolv DI and / or Rutgers Ruetasolv BP D, more preferably Rutgers Ruetasolv DI or Rutgers Ruetasolv BP D. The present invention has no particular limitation on the source of the plasticizer, and commercially available products known to those skilled in the art may be used.

[0027] In the present invention, the thermal conductive powder is preferably selected from one or more of JAZ-386, JAZ-387, and CCG060D08G, and more preferably JAZ-386, JAZ-387, or CCG060D08G. The present invention has no particular restrictions on the source of the thermal conductive powder, and commercially available products known to those skilled in the art can be used.

[0028] In the present invention, the dispersant is preferably selected from BYK BYK-9076 and / or BYK BYK-145, more preferably BYK BYK-9076 or BYK BYK-145. The present invention has no particular limitation on the source of the dispersant, and commercially available products known to those skilled in the art can be used.

[0029] In the present invention, the catalyst is preferably selected from Umicore Valikat Bi1610 and / or Vertellus Coscat 83, more preferably Umicore Valikat Bi1610 or Vertellus Coscat 83. The present invention has no particular limitation on the source of the catalyst, and commercially available products known to those skilled in the art may be used.

[0030] In the present invention, the yellow color paste can be a commercially available product well known to those skilled in the art, and the present invention has no special limitation on this.

[0031] In the present invention, the B component comprises: 2 to 10 parts by weight of isocyanate; 2 to 10 parts by weight of polyol; 2 to 10 parts by weight of plasticizer; 80 to 95 parts by weight of thermally conductive powder; 0.1 to 1 part by weight of an anti-aging agent; Dispersant 0.1 to 1 part by weight; 0.1 to 1 part by weight of water absorbent; 0.1 to 1 part by weight of blue color paste; It is preferably prepared from the following raw materials: 2 to 4 parts by weight of isocyanate; 4 to 8 parts by weight of polyol; 3 to 5 parts by weight of plasticizer; 82 to 90 parts by weight of thermally conductive powder; 0.1 to 0.2 parts by weight of anti-aging agent; 0.4 to 0.6 parts by weight of dispersant; 0.1 to 0.2 parts by weight of water absorbent; 0.1 to 0.2 parts by weight of blue color paste.

[0032] In the present invention, the polyol, plasticizer, thermal conductive powder and dispersant are the same as those in the above-mentioned component A, and are not described in detail here.

[0033] In the present invention, the isocyanate is preferably an aliphatic polyisocyanate; the aliphatic polyisocyanate is preferably Desmodur N100 and / or 4,4'-dicyclohexylmethane diisocyanate (H12MDI), more preferably Desmodur N100 or H12MDI. The present invention has no particular limitation on the source of the isocyanate, and commercially available products known to those skilled in the art may be used.

[0034] In the present invention, the anti-aging agent is preferably selected from Chinox TP-10H and / or BASF Irganox B215, more preferably Chinox TP-10H or BASF Irganox B215. The present invention has no particular limitation on the source of the anti-aging agent, and commercial products known to those skilled in the art can be used.

[0035] In the present invention, the water absorbent is preferably selected from Borchers TI and / or LANXESS Trixene ASF, more preferably Borchers TI or LANXESS Trixene ASF. The present invention has no particular limitation on the source of the water absorbent, and commercially available products known to those skilled in the art can be used.

[0036] In the present invention, the blue color paste can be a commercially available product well known to those skilled in the art, and the present invention has no special limitation on this.

[0037] The two-component polyurethane thermally conductive gel provided by the present invention adopts the above-mentioned specific components in the specific content to achieve better overall interaction, can meet the requirements for non-silicon thermal interface materials, and the product has excellent high temperature resistance and low thermal conductivity. Experimental results show that the two-component polyurethane thermally conductive gel provided by the present invention has low hardness, which is in the range of 50~70Shore-00, high thermal conductivity, and can achieve high thermal conductivity of 3.0~4.0 W / m·k. The system is easy to construct, has high extrudability, and has excellent high temperature resistance / moisture resistance. After three aging tests of PCT (high pressure cooking aging, 120℃ / 100% RH / 0.2 MPa) for 72h, high temperature and high humidity (85℃ / 85%RH) for 1000h, and high temperature (150℃ / 50%RH) for 1000h, the performance and appearance are maintained.

[0038] The present invention also provides a method for preparing the two-component polyurethane thermally conductive gel described in the above technical solution, comprising the following steps: a) Heat the polyol, plasticizer and thermal conductive powder to 110°C~130°C, mix and dehydrate in vacuum, then cool to below 50°C, add dispersant, catalyst and yellow color paste, mix in vacuum to obtain component A; b) After the isocyanate, the dehydrated polyol and the plasticizer are reacted for the first time, the dried thermal conductive powder, the antioxidant, the dispersant, the water absorbent and the blue color paste are added to carry out a second reaction to obtain component B; c) mixing the above component A and component B in a volume ratio of (0.8-1.2):1 to obtain a two-component polyurethane thermal conductive gel; There is no order restriction for step a) and step b).

[0039] In the present invention, the above-mentioned raw materials are the same as those described in the above-mentioned technical solution, and the present invention will not repeat them here.

[0040] In the present invention, the heating to 110°C~130°C mixing in step a) is preferably stirring, and the stirring speed is preferably 400rpm~600rpm, more preferably 500rpm; the vacuum degree of the vacuum dehydration is preferably -0.08MPa~-0.1MPa, and the time is preferably 1.5h~2.5h; the vacuum degree of the vacuum mixing is preferably -0.08MPa~-0.1MPa, the rotation speed is preferably 50rpm~150rpm, more preferably 100rpm, and the time is preferably 30min~60min.

[0041] In the present invention, the temperature of the first reaction in step b) is preferably 70°C to 90°C, more preferably 80°C, the rotation speed is preferably 80rpm to 120rpm, more preferably 100rpm, the vacuum degree is preferably -0.08MPa to -0.1MPa, and the time is preferably 1.5h to 2.5h; the temperature of the second reaction is preferably 10°C to 40°C, more preferably 20°C to 30°C, the rotation speed is preferably 180rpm to 220rpm, more preferably 200rpm, the vacuum degree is preferably -0.08MPa to -0.1MPa, and the time is preferably 0.5h to 1.5h.

[0042] In the present invention, the drying process in step b) is preferably specifically as follows: The thermally conductive powder is dried and dehydrated in a drying room at 90°C to 110°C for 45h to 50h to obtain a dried thermally conductive powder.

[0043] In the present invention, the dehydration process in step b) is preferably specifically as follows: The polyol and plasticizer are dehydrated at 110° C. to 130° C. under vacuum to -0.08 MPa to -0.1 MPa for 1.5 h to 2.5 h to obtain dehydrated polyol and plasticizer.

[0044] The preparation method provided by the invention has simple process, mild conditions, easy control, low requirements on equipment, and has broad application prospects.

[0045] The invention provides a two-component polyurethane thermally conductive gel, which is composed of a component A and a component B in a volume ratio of (0.8-1.2):1; the component A comprises: 5-15 parts by weight of polyol; 1-10 parts by weight of plasticizer; 80-95 parts by weight of thermally conductive powder; 0.1-1 part by weight of dispersant; 0.1-1 part by weight of catalyst; and 0.1-1 part by weight of yellow color paste; the component B comprises: 2-10 parts by weight of isocyanate; 2-10 parts by weight of polyol; 2-10 parts by weight of plasticizer; 80-95 parts by weight of thermally conductive powder; 0.1-1 part by weight of anti-aging agent; 0.1-1 part by weight of dispersant; 0.1-1 part by weight of water absorbent; and 0.1-1 part by weight of blue color paste. Compared with the prior art, the two-component polyurethane thermally conductive gel provided by the present invention adopts specific components in specific contents to achieve better overall interaction, which can meet the requirements for non-silicon thermal interface materials. At the same time, the product has excellent high temperature resistance and low thermal conductivity.

[0046] In addition, the preparation method provided by the present invention has simple process, mild conditions, easy control, low requirements on equipment, and has broad application prospects.

[0047] In order to further illustrate the present invention, the following examples are provided for detailed description. The raw materials involved in the following examples of the present invention are as follows: Polyol: Flexible aliphatic modified castor oil polyol, Itoh Oil URIC 4048U, Itoh Oil URICPH-100D; Plasticizer: hydrocarbon high boiling point plasticizer, Rutgers Ruetasolv DI, Rutgers Ruetasolv BP D; Thermal conductive powder: JAZ-386, JAZ-387, CCG060D08G; Dispersants: BYK BYK-9076, BYK BYK-145; Catalysts: Umicore Valikat Bi1610, Vertellus Coscat 83; Yellow color paste: Bomax 085-1I4215; Isocyanate: Covestro aliphatic polyisocyanate (HDI biuret) Desmodur N 100, Wanhua 4,4'-dicyclohexylmethane diisocyanate (H12MDI); Anti-aging agent: Taiwan Double Bond Chinox TP-10H, BASF Irganox B215; Water absorbent: Borchers TI, LANXESS Trixene ASF; Blue color paste: Baomeishi 085-5M4214.

[0048] Example 1 Component A: 10 parts by weight of URIC PH-100D polyol, 3 parts by weight of Ruetasolv BP D plasticizer, 85 parts by weight of CCG060D08G thermal conductive powder, 0.5 parts by weight of BYK-9076 dispersant, 1 part by weight of Valikat Bi1610 catalyst, and 0.5 parts by weight of yellow color paste; Component B: 4 parts by weight of Desmodur N100 isocyanate, 8 parts by weight of URIC PH-100D polyol, 5 parts by weight of Ruetasolv BP D plasticizer, 82 parts by weight of CCG060D08G thermal conductive powder, 0.2 parts by weight of Chinox TP-10H anti-aging agent, 0.5 parts by weight of BYK-9076 dispersant, 0.1 parts by weight of TI water absorbent, and 0.2 parts by weight of blue color paste.

[0049] Example 2 Component A: 8 parts by weight of URIC PH-100D polyol, 2 parts by weight of Ruetasolv DI plasticizer, 88 parts by weight of JAZ-386 thermal conductive powder, 0.5 parts by weight of BYK-145 dispersant, 1 part by weight of Valikat Bi1610 catalyst, and 0.5 parts by weight of yellow color paste; Component B: 3 parts by weight of H12MDI isocyanate, 6 parts by weight of URIC 4048U polyol, 5 parts by weight of Ruetasolv DI plasticizer, 85 parts by weight of JAZ-386 thermal conductive powder, 0.2 parts by weight of Chinox TP-10H anti-aging agent, 0.5 parts by weight of BYK-145 dispersant, 0.1 parts by weight of TI water absorbent, and 0.2 parts by weight of blue color paste.

[0050] Example 3 Component A: 5 parts by weight of URIC 4048U polyol, 1 part by weight of Ruetasolv DI plasticizer, 92 parts by weight of JAZ-387 thermal conductive powder, 0.5 parts by weight of BYK-145 dispersant, 1 part by weight of Coscat 83 catalyst, and 0.5 parts by weight of yellow color paste; Component B: 2 parts by weight of H12MDI isocyanate, 4 parts by weight of URIC 4048U polyol, 3 parts by weight of Ruetasolv DI plasticizer, 90 parts by weight of JAZ-387 thermal conductive powder, 0.2 parts by weight of Irganox B215 antioxidant, 0.5 parts by weight of BYK-145 dispersant, 0.1 parts by weight of Trixene ASF water absorbent, and 0.2 parts by weight of blue color paste.

[0051] The above formula is shown in Table 1 below.

[0052] Table 1 The specific preparation methods of the two-component polyurethane thermally conductive gel provided in the above embodiments are as follows: Component A: Heat the polyol, plasticizer and thermal conductive powder to 120°C with stirring at 500 rpm, evacuate to -0.09 MPa for dehydration for 2 hours, then cool to below 50°C, add dispersant, catalyst and yellow color paste, evacuate to below -0.09 MPa, continue stirring at 100 rpm for 40 minutes to obtain component A.

[0053] Component B: First, dry and dehydrate the thermal conductive powder in a drying room at 100°C for 48 hours and set aside; The polyol and plasticizer were vacuumed to -0.09 MPa at 120°C and dehydrated for 2 h for later use; Then, isocyanate, pre-dehydrated polyol, and plasticizer were stirred at 100 rpm at 80°C and evacuated to -0.09 MPa for 2 hours, and then pre-dried thermal conductive powder was added, and anti-aging agent, dispersant, water absorbent, and blue color paste were added. The mixture was stirred at 200 rpm at room temperature and evacuated to -0.09 MPa for 1 hour to obtain component B.

[0054] Finally, the above-mentioned component A and component B are evenly mixed in a volume ratio of 1:1 to obtain a two-component polyurethane thermal conductive gel.

[0055] The various properties of the two-component polyurethane thermally conductive gel provided in each embodiment were tested, and the test standards / methods are as follows: Density: ASTM D792, Test Method for Density and Relative Density of Plastics; Hardness: ASTM D2240, Standard Test Method for Durometer Hardness; Thermal conductivity: ASTM D5470, Standard test method for thermal conductivity of thermally conductive electrical insulating materials; Volume resistivity: ASTM D257, Standard Test Method for DC Resistance or Conductance of Insulating Materials; Breakdown voltage: ASTM D149, Test method for dielectric breakdown voltage and dielectric strength of solid electrical insulating materials at industrial power frequencies; PCT aging (120℃ / 100% RH / 0.2 MPa): IEC60068-2-66, Environmental testing-Part 2: Test methods-Test Cx: Damp heat, steady state (unsaturatedpressurized vapor); High temperature and high humidity aging (85℃ / 85%RH): GB / T 2423.50-2012, Environmental testing for electrical and electronic products Part 2: Test method Steady humidity and heat is mainly used for accelerated testing of components; High temperature aging (150℃ / 50%RH): GB / T 2423.50-2012, Environmental testing for electric and electronic products Part 2: Test method Steady state damp heat is mainly used for accelerated testing of components.

[0056] Some test results are shown in Table 2 below.

[0057] Table 2 In Table 2, control 1 glue: two-component silicone thermal conductive gel, Hangzhou Zhijiang ZJ-DR6200-4; control 2 glue: single-component MS thermal conductive gel, Zhejiang Sanyuan SG450F.

[0058] PCT aging (120℃ / 100% RH / 0.2 MPa) hardness change curve see Figure 1 As shown; high temperature and high humidity aging (85℃ / 85%RH) hardness change curve see Figure 2 As shown; high temperature aging (150℃ / 50%RH) hardness change curve see Figure 3 shown.

[0059] Experimental results show that the two-component polyurethane thermally conductive gel provided by the present invention firstly prepares an isocyanate prepolymer with a low NCO content to increase the length of the overall chain segment, increase the flexibility of the glue, and reduce the hardness of the glue; secondly, by selecting a suitable combination of thermally conductive powder + dispersant, the viscosity of the system is reduced, the amount of thermally conductive powder added is increased, and the extrusion of the glue is improved; thirdly, by selecting a suitable flexible polyol, the hardness of the glue is further reduced, and a suitable anti-aging agent and a high-temperature resistant plasticizer are matched to improve the weather resistance of the glue; from the results, through reasonable raw material selection, the thermally conductive gel prepared by the polyurethane system can have a thermal conductivity of up to 4.5W / m / k, and the hardness can be controlled below 70Shore-00, which is basically consistent with the matching of silicone; more importantly, the polyurethane thermally conductive gel has excellent aging resistance and high temperature resistance. Whether it is extreme PCT aging or high temperature aging at 150°C, the glue does not show abnormal phenomena such as cracking and powdering, and the hardness is well maintained.

[0060] In summary, this invention realizes the development of non-silicone series thermal conductive gel through reasonable formula design, which solves the shortcomings of polyurethane thermal conductive gel such as not being resistant to high temperature and having low thermal conductivity.

[0061] By adding liquid polybutadiene polyol to the system, the water vapor permeability of the two-component polyurethane water-blocking adhesive can be reduced, and by adding antioxidants, the resistance of the adhesive to ultraviolet radiation can be improved; more importantly, the addition of asphalt has a positive effect on the system. With the increase in the amount of asphalt added, the water vapor permeability of the system gradually decreases, the flexibility is improved, and the resistance to PCT / ultraviolet radiation aging is improved. However, it is worth noting that excessive asphalt addition will reduce the hardness and bonding strength of the system. From the test results, adding 20wt% is the best, and further increasing it to 30wt% will reduce the shear strength of the system. The experimental results of the comparative example show that when no asphalt is added, the resistance to ultraviolet radiation of the system is significantly attenuated.

[0062] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A two-component polyurethane thermal conductive gel, consisting of component A and component B in a volume ratio of (0.8~1.2):1; The A component comprises: 5 to 15 parts by weight of polyol; 1 to 10 parts by weight of plasticizer; 80 to 95 parts by weight of thermally conductive powder; Dispersant 0.1 to 1 part by weight; 0.1 to 1 part by weight of catalyst; 0.1 to 1 part by weight of yellow color paste; The B component includes: 2 to 10 parts by weight of isocyanate; 2 to 10 parts by weight of polyol; 2 to 10 parts by weight of plasticizer; 80 to 95 parts by weight of thermally conductive powder; 0.1 to 1 part by weight of an anti-aging agent; Dispersant 0.1 to 1 part by weight; 0.1 to 1 part by weight of water absorbent; 0.1 to 1 part by weight of blue color paste.

2. The two-component polyurethane thermally conductive gel according to claim 1, characterized in that: The polyol is a flexible aliphatic modified castor oil polyol.

3. The two-component polyurethane thermally conductive gel according to claim 1, characterized in that: The plasticizer is a hydrocarbon high boiling point plasticizer.

4. The two-component polyurethane thermally conductive gel according to claim 1, characterized in that: The thermal conductive powder is selected from one or more of Jinge JAZ-386, Jinge JAZ-387, and Zexi CCG060D08G.

5. The two-component polyurethane thermally conductive gel according to claim 1, characterized in that: The dispersant is selected from BYK BYK-9076 and / or BYK BYK-145.

6. The two-component polyurethane thermally conductive gel according to claim 1, characterized in that: The catalyst is selected from Umicore Valikat Bi1610 and / or Vertellus Coscat 83.

7. The two-component polyurethane thermally conductive gel according to claim 1, characterized in that: The isocyanate is an aliphatic polyisocyanate; The water absorbent is selected from Borchers TI and / or LANXESS Trixene ASF.

8. A method for preparing the two-component polyurethane thermally conductive gel according to any one of claims 1 to 7, comprising the following steps: a) Heat the polyol, plasticizer and thermal conductive powder to 110°C~130°C, mix and dehydrate in vacuum, then cool to below 50°C, add dispersant, catalyst and yellow color paste, mix in vacuum to obtain component A; b) After the isocyanate, the dehydrated polyol and the plasticizer are reacted for the first time, the dried thermal conductive powder, the antioxidant, the dispersant, the water absorbent and the blue color paste are added to carry out a second reaction to obtain component B; c) mixing the above component A and component B in a volume ratio of (0.8-1.2):1 to obtain a two-component polyurethane thermal conductive gel; There is no order restriction for step a) and step b).

9. The preparation method according to claim 8, characterized in that: The mixing method of heating to 110° C. to 130° C. in step a) is stirring, and the stirring speed is 400 rpm to 600 rpm; The vacuum degree of the vacuum dehydration is -0.08MPa~-0.1MPa, and the time is 1.5h~2.5h; The vacuum degree of the vacuum mixing is -0.08MPa~-0.1MPa, the rotation speed is 50rpm~150rpm, and the time is 30min~60min.

10. The preparation method according to claim 8, characterized in that: The temperature of the first reaction in step b) is 70°C to 90°C, the rotation speed is 80rpm to 120rpm, the vacuum degree is -0.08MPa to -0.1MPa, and the time is 1.5h to 2.5h; The temperature of the second reaction is 10°C to 40°C, the rotation speed is 180rpm to 220rpm, the vacuum degree is -0.08MPa to -0.1MPa, and the time is 0.5h to 1.5h.

Citation Information

Patent Citations

  • Preparing method and application of anti-freezing type bi-component polyurea waterproof paint for bridges

    CN106010175A

  • Preparation and using method of organic silicon-polyurea self-stratifying coating

    CN107298930A

  • High-heat-resistance two-component polyurethane structural adhesive for power battery and preparation method of high-heat-resistance two-component polyurethane structural adhesive

    CN116751558A

  • Silicon-free polyurethane heat-conducting gel and preparation method thereof

    CN117362568A

  • Two-part interface materials, systems including the interface material, and methods thereof

    US20220213249A1